Efekti infuzije ultrakratko delujućeg beta-blokatora esmolola na kardiovaskularne parametre i kvalitet postoperativnog oporavka kod pacijenata planiranih za elektivnu plastičnu hirurgiju - Lončar-Stojiljković, Dragana B. (Scripta Medica, 2021)
Background/Aim: Esmolol is an ultra-short-acting, easily titratable β-adrenergic receptor antagonist used for urgent treatment of hypertension and tachycardia in non-surgical and surgical settings. Aim of this clinical study was to investigate its cardiovascular effects and quality of the emergence from anaesthesia in patients scheduled for elective plastic surgery under general balanced anasthesia.Methods: A total of 30 ASA I/II patients were randomised in two groups of similar demographic characteristics and baseline values of cardiovascular parameters. Esmolol group received esmolol dissolved in glucose 5 % as an intravenous infusion, 0.3 mg/kg/min during the first 5 min and at a rate of 0.1 mg/kg/min thereafter. Control patients received the solvent only, at the same rate and volume. General balanced anaesthesia was induced with thiopentone sodium and fentanyl and maintained with nitrous oxide and oxygen. Neuromuscular relaxation was assured with pancuronium bromide and was antagonised at the end of operation with atropine and neostigmine. Systolic and diastolic blood pressure and heart rate were registered at all ctritical phases: (1) immediately prior to the induction (baseline value), (2) induction to anaesthesia, (3) tracheal intubation, (4) first skin incision, (5) surgical manipulation with organs, (6) suture of the surgical wound and (7) tracheal extubation. Dug consumption and quality of postoperative recovery were monitored.Results: In most of the critical phases of anaesthesia and operation, patients from the Esmolol group had significantly lower values of cardiovascular parameters than the patients from the Control group. Esmolol-treated patients needed less fentanyl, droperidol and pancuronium and had faster and smoother emergence from anaesthesia than the control patients.Conclusion: Esmolol improved haemodynamics and post-anaesthesia recovery in patients undergoing elective plastic surgery under general balanced anaesthesia.
Keywords: Esmolol; Beta-blokatori; Anestezija; Plastična hirurgija; Kardiovaskularni parametri